Epistemes otras y cambio social: sentidos de lo interdisciplinario - Rueda Barrera, Eduardo A. (2024)
The paper addresses the significant role that other forms of knowledge must play in the construction of alternatives to overcome the most pressing problems faced by today's global societies, namely: local and global environmental degradation, social inequality and inequity, and violent conflict at various scales. To do so, it characterizes and provides reasons to validate other forms of knowledge, particularly those anchored in the social experience of indigenous peoples, women, and laypeople, and advocates for an understanding of interdisciplinarity as an ethical-political agency obligated to open, for transformative purposes, paths of dialogue between such forms of knowledge and academic disciplines. The purpose of this dialogue is not other that catalyzing, through the effects of such forms of knowledge, the production of genuinely innovative visions and practices in the face of the challenges that confront us today.